Reversibility of the zinc-blende to rock-salt phase transition in cadmium sulfide nanocrystals - Martín-Rodríguez, R.; González, J.; Valiente, R.; Aguado, F.; Santamaría-Pérez, D.; Rodríguez, F. (Journal of applied physics, 2012)
CdS nanoparticles prepared by a mechanochemical reaction in a planetary ball mill have been investigated by x-ray diffraction, optical absorption, and Raman scattering under high pressure conditions up to 11 GPa. The zinc-blende (ZB) to rock-salt phase transition is observed around 6 GPa in all experiments, the transition pressure being similar to the one measured in CdS colloidal nanocrystals, and much higher than in bulk (around 3 GPa). The direct optical energy gap in ZB-CdS increases with pressure, and suddenly drops when the pressure is raised above 6 GPa, according to the high-pressure indirect-gap behavior. A linear blue-shift of the CdS Raman spectra is observed upon increasing pressure. Both Raman and x-ray diffraction studies indicate that the phase transition has a large hysteresis, making the ZB phase barely recoverable at ambient conditions. Cell parameters and bulk modulus measured in CdS nanoparticles clearly show that the nanoparticles at ambient conditions are subject to an initial pressure in comparison to CdS bulk.